2009
DOI: 10.1097/jcp.0b013e3181aba6a4
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a Combination of Flumazenil and Gabapentin in the Treatment of Alcohol Dependence

Abstract: Improved treatment of alcohol dependence is a high priority, including defining subtypes that might respond differently. We evaluated a medication combination of intravenous flumazenil (FMZ) and oral gabapentin (GBP) in alcoholics who did and did not exhibit pretreatment alcohol withdrawal (AW) symptoms. Sixty alcohol-dependent individuals (44 with low AW and 16 with high AW) were randomized to receive FMZ (2 mg of incremental bolus for 20 minutes for 2 consecutive days) and GBP (up to 1200 mg nightly for 39 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
72
0
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(79 citation statements)
references
References 40 publications
3
72
0
4
Order By: Relevance
“…Anton et al [89] studied 60 alcohol-dependent patients who received 2 days of intravenous flumazenil (2 mg incremental bolus × 20 min) to ensure complete withdrawal followed by gabapentin (up to 1200 mg at bedtime for 39 days) or intravenous/oral placebos. The low-alcohol withdrawing group had an increased percentage of drinking days and hastened time to first HDD when randomized to the active medication while the high-alcohol withdrawing subjects displayed the reverse profile.…”
Section: Anticonvulsants For the Treatment Of Harmful Drinking Pattmentioning
confidence: 99%
“…Anton et al [89] studied 60 alcohol-dependent patients who received 2 days of intravenous flumazenil (2 mg incremental bolus × 20 min) to ensure complete withdrawal followed by gabapentin (up to 1200 mg at bedtime for 39 days) or intravenous/oral placebos. The low-alcohol withdrawing group had an increased percentage of drinking days and hastened time to first HDD when randomized to the active medication while the high-alcohol withdrawing subjects displayed the reverse profile.…”
Section: Anticonvulsants For the Treatment Of Harmful Drinking Pattmentioning
confidence: 99%
“…Others reported that gabapentin worked better than placebo in preventing relapse in patients who had undergone benzodiazepine detoxification, but did not compare them to non-detoxified individuals (10). Our group recently reported that gabapentin worked significantly better than placebo only in those with clinically significant alcohol withdrawal at the time of study entry (11). In that study gabapentin was adjunctive to an initial intravenous flumazenil, so the direct effect of gabapentin, by itself could not be validly affirmed.…”
Section: Discussionmentioning
confidence: 99%
“…Since clinician soften cannot predict, a priori, what sort of symptoms specific individuals will exhibit as well as what sort of craving (withdrawal based versus reward based) will be the most salient, it might be wise to attempt to reduce both in order to improve treatment efficacy. We and others have previously shown that anticonvulsants in general (5) (6) (7) and gabapentin in particular (1) (8) (9) were able to ameliorate acute alcohol withdrawal and could actually be useful in preventing relapse (10) especially in those with previous alcohol withdrawal symptoms (11). Gabapentin, which works by modulating both GABA and glutamate tone, is an especially appealing drug since it hypothetically can “normalize” the known GABA deficits and glutamate excess that is thought to underlie alcohol withdrawal (12) and perhaps parts of the early abstinence, or protracted withdrawal syndrome (13).…”
Section: Introductionmentioning
confidence: 99%
“…Los pacientes efectuaron un seguimiento ambulatorio con determinaciones de sustancias en la orina 3 veces por semana (lunes, miércoles y viernes) y 1 visita médica cada 4 semanas, durante 12 semanas. El resultado del tratamiento fue evaluado mediante la variable tiempo hasta el primer consumo excesivo de alcohol (TPCEA), de acuerdo con otros estudios de tratamiento del alcoholismo 22,23 .…”
Section: Procedimientounclassified
“…Urine samples were collected for analysis three times a week (Monday, Wednesday and Friday). Outcome was assessed by means of the time to first heavy drinking day (TFHD) variable 22,23 .…”
Section: Methodsmentioning
confidence: 99%